UJI PENERIMAAN PRODUK BERDASARKAN FORMULASI DAN UJI SENSORIS MSG ORGANIK CAIR BAHARAT - Wicaksono, M Galih; Tias, Eriza Putri Ayu Ning; Setyaningsih, Endang (UHAMKA PRESS, 2024)
Organik MSG needs to be developed because now many foods found in supermarkets, restaurants, and school cafeterias use MSG additives which can have negative consequences for public health. The purpose of this article is to determine the public's acceptance of liquid organic MSG based on tempe and pineapple. The method used is the product acceptance test by the 50 panelists through experiencing the product directly with 3 kinds of formulations. The results of the product acceptance test are complemented by the results of the sensory test and hedonic test from the BPSMB laboratory. The data obtained were processed using the Krusskal Wallys test and the Mann-Whitney follow-up test. The results of all tests showed that the level of preference for the color, aroma, taste, and texture of liquid organic MSG (BAHARAT) with the substitution of hydrolyzate tempe and pineapple extract was not significantly different (P> 0,05) in F1 and F2. However, there was a significant difference (P<0,05) in F1 with F3 and F2 with F3 in the level of preference for color, aroma, taste, and texture of liquid organic MSG with the substitution of tempe hydrolyzate and pineapple extract. The best liquid organic MSG (BAHARAT) product formula is at F2 or with product code 758 or the composition of tempe hydrolyzate with pineapple extract is 1:2 based on differentiation and hedonic tests.